Visible Light Photocatalytic Reduction of O‐Thiocarbamates: Development of a Tin‐Free Barton–McCombie Deoxygenation Reaction. Issue 13 (11th September 2014) - Chenneberg, Ludwig; Baralle, Alexandre; Daniel, Marion; Fensterbank, Louis; Goddard, Jean‐Philippe; Ollivier, Cyril
Abstract The Barton–McCombie deoxygenation is one of the most important transformations in the toolbox of organic chemists which has been the subject of a number of methodological developments. In this study, we report a photocatalyzed redox deoxygenation of secondary and tertiary alcohols from thiocarbamate precursors under visible light activation. The iridium complex Ir(ppy)3 proved to be the most efficient catalyst in the presence of Hünig's base as sacrifial electron donor. A mechanistic investigation is presented based on fluorescence quenching experiments and cyclic voltammetry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>